2020
DOI: 10.1016/j.psychres.2019.112702
|View full text |Cite
|
Sign up to set email alerts
|

Self-help interventions to reduce self-stigma in people with mental health problems: A systematic literature review

Abstract: People with mental health problems often experience self-stigma, whereby they internalise stereotypic or stigmatising views held by others. Self-stigma is known to have negative effects on self-esteem and self-efficacy and a continuing impact on psychological wellbeing. Self-help interventions designed to reduce self-stigma may have an important contribution to make. This review aimed to provide an overview and critical appraisal of the literature on self-help interventions that target self-stigma related to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…No evidence (i.e., systematic reviews or primary intervention studies) was identified for stigma-reduction directly in relation to COVID-19, SARS/MERS, influenza or Ebola. Most reviews included evidence from studies using a broad range of quantitative designs (generally this included randomised-control trials or RCTs) (Clement et al, 2013;Mehta et al, 2015;Hanisch et al, 2016;Feyissa et al, 2019;Ma et al, 2019;Pantelic et al, 2019), one focused on RCTs specifically (Büchter and Messer, 2017), and some included evidence from quantitative, qualitative and/or mixed methods studies (Sermrittirong et al, 2014;Sommerland et al, 2017;Heim et al, 2018;Andersson et al, 2019;Mills et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No evidence (i.e., systematic reviews or primary intervention studies) was identified for stigma-reduction directly in relation to COVID-19, SARS/MERS, influenza or Ebola. Most reviews included evidence from studies using a broad range of quantitative designs (generally this included randomised-control trials or RCTs) (Clement et al, 2013;Mehta et al, 2015;Hanisch et al, 2016;Feyissa et al, 2019;Ma et al, 2019;Pantelic et al, 2019), one focused on RCTs specifically (Büchter and Messer, 2017), and some included evidence from quantitative, qualitative and/or mixed methods studies (Sermrittirong et al, 2014;Sommerland et al, 2017;Heim et al, 2018;Andersson et al, 2019;Mills et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the systematic reviews providing evidence for this review are presented in Table 1 (added details in online Supplementary Materials). These reviews reported on the effectiveness of anti-stigma interventions in relation to leprosy (Sermrittirong et al 2014), tuberculosis (Sommerland et al 2017), HIV/AIDS (Andersson et al 2019;Feyissa et al 2019;Ma et al 2019;Pantelic et al 2019), and mental illness (Büchter & Messer 2017;Clement et al 2013;7 Hanisch et al 2016;Heim et al 2018;Mehta et al 2015;Mills et al 2020). In terms of stigma, most reviews focused on general stigma in relation to the condition (Clement et al 2013;Feyissa et al 2019;Hanisch et al 2016;Heim et al 2018;Ma et al 2019;Mehta et al 2015;Pantelic et al 2019;Sermrittirong et al 2014;Sommerland et al 2017), but self-stigma (Büchter & Messer 2017;Mills et al 2020), and enacted, anticipated or internalised stigma (Andersson et al 2019) were also considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that dance may also offer a way for some people with mental health difficulties to experience a sense of freeing up their minds and an opportunity to escape their immediate concerns for a period (Frogitt and Little 2012). Many people with mental health difficulties experience selfstigma (Mills et al 2020). Dance, as a socially prescribed intervention may help reduce this, by offering an activity that is not immediately associated with an illness or pathology model of mental health, however further research is needed to confirm if this is the case.…”
Section: Implications For Mental Health Nursing Practicementioning
confidence: 99%
“…Stigma may negatively influence mental wellbeing. A substantial body of literature exists about the ways in which the stigma of conditions such as schizophrenia, mood disorders, substance disorders or HIV-AIDS and self-stigma combine to create depression, demoralization on one hand and lower self-esteem on the other ( Livingston and Boyd 2010 ; Mills, et al 2019 ; Pellet, et al 2019 ). Furthermore, it has been shown that depression and self-esteem are directly connected ( Mruk 2006 ).…”
Section: Introductionmentioning
confidence: 99%